2019
DOI: 10.1371/journal.pone.0226349
|View full text |Cite
|
Sign up to set email alerts
|

Differences in receipt of opioid agonist treatment and time to enter treatment for opioid use disorder among specialty addiction programs in the United States, 2014-17

Abstract: BackgroundAccess to adequate treatment for opioid use disorder (OUD) has been a high priority among American policymakers. Elucidation of the sociodemographic and institutional differences associated with the use, or lack thereof, of opioid agonist therapy (OAT) provides greater clarity on who receives OAT. Timely access to care is a further consideration and bears scrutiny as well.MethodsWe draw upon data from the Treatment Episode Data Set—Admissions (TEDS-A) to analyse the relationship between sociodemograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
3
6
0
Order By: Relevance
“…Consistent with existing literature examining MOUD access in the general population, this systematic review found younger age to be negatively associated with MOUD access. In addition, the findings suggest that younger age was positively associated with accessing opioid antagonists and partial opioid agonists, such as naltrexone and buprenorphine-naloxone, respectively.…”
Section: Discussionsupporting
confidence: 85%
“…Consistent with existing literature examining MOUD access in the general population, this systematic review found younger age to be negatively associated with MOUD access. In addition, the findings suggest that younger age was positively associated with accessing opioid antagonists and partial opioid agonists, such as naltrexone and buprenorphine-naloxone, respectively.…”
Section: Discussionsupporting
confidence: 85%
“…58 Another study investigating socioeconomic determinants of planned methadone treatment noted that those who were not experiencing homelessness were more likely to receive methadone as part of their treatment 59 and a later study found that experiencing homelessness was associated with decreased odds of receiving MOUD and also lower odds of waiting greater than 1 week to enter treatment. 16 Similarly a study of the use of methadone within “detoxification” settings found those experiencing homelessness were less likely to have methadone planned for their treatment. 15 The present study’s results build off these studies by demonstrating that, in addition to the disparities that may limit treatment entry into MOUD, those individuals experiencing homelessness that are able to enroll into MOUD have reduced retention length and decreased odds of treatment completion.…”
Section: Discussionmentioning
confidence: 99%
“…14 While many people with OUD receive non-MOUD treatments, 15 PEH with OUD who enter SUD treatment are less likely than their housed counterparts to receive MOUD. [16][17][18] Expanding engagement in evidence-based OUD treatment is even more important in the face of the aforementioned worsening overdose crisis, which disproportionately impacts PEH.…”
Section: Introductionmentioning
confidence: 99%
“…5 Although recent data suggest that the prevalence of OUD and its negative consequences may be increasing among women, a recent study using national data on SUD treatment admissions found that women had slightly higher odds of receiving medication for OUD than men. 24 Historically, services tailored to women (eg, women’s recovery groups, child care) have generally been considered beneficial but not necessary, leading to their underuse in OUD treatment settings. 25 The higher proportion of OUD among women compared with men with a need for SUD treatment further supports previous evidence, 6,13 endorsing the need for universal adoption of gender-informed treatment for people with OUD.…”
Section: Discussionmentioning
confidence: 99%
“…OUD than men. 24 Historically, services tailored to women (eg, women's recovery groups, child care) have generally been considered beneficial but not necessary, leading to their underuse in OUD treatment settings. 25 The higher proportion of OUD among women compared with men with a need for SUD treatment further supports previous evidence, 6,13 endorsing the need for universal adoption of gender-informed treatment for people with OUD.…”
Section: Discussionmentioning
confidence: 99%